Screening and surveillance for hereditary colorectal cancer - Hee Man Kim; Tae Il Kim (Intestinal Research, 2024)
Hereditary colorectal cancer is a type of cancer that is caused by a genetic mutation. Individuals with a family history of colorectal cancer, or who have a known hereditary syndrome, are at an increased risk of developing the disease. Screening and surveillance are important tools for managing the risk of hereditary colorectal cancer. Screening involves a combination of tests that can detect precancerous or cancerous changes in the colon and rectum. Surveillance involves regular follow-up examinations to monitor disease progression and to identify new developments. The frequency and type of screening and surveillance tests may vary depending on an individual’s risk factors, genetic profile, and medical history. However, early detection and treatment of hereditary colorectal cancer can significantly improve patient outcomes and reduce mortality rates. By implementing comprehensive screening and surveillance strategies, healthcare providers can help individuals at risk of hereditary colorectal cancer to receive timely interventions and make informed decisions about their health. Specific examples of screening and surveillance tests for hereditary colorectal cancer include colonoscopy, genetic testing, and imaging tests. In this review article, we will discuss detailed screening and surveillance of hereditary colorectal cancer.